The Geography of Talent: Development Implications and Long-Run Prospects - Michal Burzyński; Christoph Deuster; Frédéric Docquier (Fondation pour les études et recherches sur le développement international (FERDI), 2018)
This paper characterizes the recent evolution of the geographic distribution of talent, and studies its implications for development inequality. Assuming the continuation of recent educational and immigration policies, it produces integrated projections of income, population, urbanization and human capital for the 21st century. To do so, we develop and parameterize a two-sector, two-class, world economy model that endogenizes education decisions, population growth, labor mobility, and income disparities across countries and across regions/sectors (agriculture vs. nonagriculture). We find that the geography of talent matters for global inequality, whatever the size of technological externalities. Low access to education and the sectoral allocation of talent have substantial impacts on inequality, while the effect of international migration is small. We conclude that policies targeting access to all levels of education and sustainable urban development are vitalto reduce demographic pressures and global inequality in the long term.
Keywords: E24; J24; O15; 330; human capital; migration; Urbanization; growth; inequality.